Resolusi Konflik dan Islam Nusantara: Memromosikan Dialog antar Budaya dan Rekognisi Sosial - Masykur Wahid (Refleksi, 2016)
This paper is a philosophical study about conflicts resolution and Islam Nusantara among multicultural societies. This article discusses the relationships between individuals who produce social conflicts of ethnic and religious nuance. Referring to the theory of multiculturalism from Bhikhu Parekh, literature study method, phenomenology of religious life method, and critical reflection method, it is concluded that the social conflicts (a) emerged from an individual behavior that interprets moral and cultural in different view; and (b) happened in countries that provide political uniformity. These social conflicts should be cultivated by an individual through cultural dialogues and the actions of intercultural dialogue and social recognition. The dialogue is expected to rediscover harmony in social life.